Assessment of temporomandibular disorder and occlusion in treated class III malocclusion patients - Karyna Valle-Corotti; Arnaldo Pinzan; Caio Vinícius Martins do Valle; Ana Carla Raphaelli Nahás; Mauro Vinícius Corotti (University of São Paulo, 2007)
OBJECTIVE: The aims of this study were to compare the prevalence of temporomandibular disorders (TMD) in individuals submitted to either orthodontic or ortho-surgical Class III malocclusion treatment and to assess the influence of occlusal aspects on TMD severity. MATERIAL AND METHODS: The sample consisted of 50 individuals divided into two groups, according to the type of treatment (orthodontic or orthodontic with orthognathic surgery). The presence of signs and symptoms of TMD was evaluated by an anamnestic questionnaire and a clinical examination, including TMJ and muscle palpation, active mandibular range of motion, joint noises and occlusal examination. RESULTS: Based on the anamnestic questionnaire, 48% had no TMD, 42% had mild TMD and 10% had moderate TMD. The presence and severity of TMD did not show any relationship with the type of orthodontic treatment (p>0.05). The chi-square test showed a positive association (p<0.05) between TMD and non-working side occlusal interferences. CONCLUSION: Based on the methodology used and the results obtained, it may be concluded that Class III orthodontic treatment was not associated with the presence of TMD signs and symptoms and the non-working side contacts can be occlusal factors of risk. There was no significant difference in TMD prevalence between the studied groups (orthodontically treated patients and patients treated with orthodontics followed by orthognathic surgery).